20 ways to draw a tulip and 44 other fabulous flowers : a sketchbook for artists, designers, and doodlers - Congdon, Lisa (Quarry Books, 2014)
This inspiring sketchbook is part of the new 20 Ways series from Quarry Books, designed to offer artists, designers, and doodlers a fun and sophisticated collection of illustration fun. Each spread features 20 inspiring illustrated examples of 45 themes tulips, roses, dahlias, and much, much more over 900 drawings, with blank space for you to draw your take on 20 Ways to Draw a Tulip.